The Development of UTHM Campus Event Management System using Laravel Framework - Ainul Hisham, Ainul Aisyah; Mohd Zin, Nur Ariffin (Applied Information Technology And Computer Science, 2025)
Universiti Tun Hussein Onn Malaysia (UTHM) hosts over 70 clubs, yet the MyAktiviti portal is managed by Pejabat Hal Ehwal Pelajar lacks public events registration features and detailed club information. This limitation reduces student engagement and clubs’ visibility, as essential data such as club objectives, description, contact details, and list of upcoming events are not readily accessible. Thus, the UTHM Campus Event Management System was developed to centralize stakeholder activities and improve efficiency across the university. Built using the Prototype Model, the system uses Laravel-PHP for the backend development, MySQL for database management, and HTML, CSS and JavaScript for a dynamic frontend. It was refined iteratively based on feedback from stakeholders. User-acceptance testing involving representative stakeholders reported an 84.8% satisfaction rate, indicating improved event planning, coordination and student engagement. Future development will focus on adding mobile access and analytics modules to personalize recommendations and support larger user loads.